An exceptionally well-preserved herbaceous eudicot from the Early Cretaceous (late Aptian–early Albian) of Northwest China. Issue 12 (4th May 2021) - Du, Baoxia; Zhang, Mingzhen; Sun, Bainian; Li, Aijing; Zhang, Jing; Yan, Defei; Xie, Sanping; Wu, Jingyu
Abstract: A fossil eudicot, Gansufructus saligna gen. et sp. nov., is reported from the Early Cretaceous (late Aptian–early Albian) of the Gansu Province, Northwest China, based on numerous well-preserved axes with attached leaves and infructescences. The leaves are alternate, short petiolate and linear-lanceolate with low rank pinnate to reticulate venation. The infructescences are loose panicles bearing fruits in different stages of maturity, each containing four partly free carpels borne in a whorled arrangement. Each carpel has three to five seeds borne along its ventral margin. The nature of the leaves and axes indicates a terrestrial, herbaceous habit. In general organization, Gansufructus is closely similar to the fruit-bearing axes of Sinocarpus decussatus from the Early Cretaceous Jehol Biota, as well as other more or less contemporaneous angiosperms from the Far East, which together provide evidence of diverse eudicot angiosperms of low stature colonizing areas close to environments of deposition. Abstract : An exceptionally well-preserved herbaceous eudicot was reported from the Early Cretaceous of Northwest China, providing important insights into the morphology, diversification and ecological environments of early angiosperms.